Attenuation of Hippocampal Evoked Potentials in vivo by Activation of GtACR2, an Optogenetic Chloride Channel - Acharya, Anirudh R.; Larsen, Lars Emil; Van Lysebettens, Wouter; Wadman, Wytse Jan; Delbeke, Jean; Vonck, Kristl; Meurs, Alfred; Boon, Paul; Raedt, Robrecht (Frontiers in Neuroscience, 2021)
Aim GtACR2, a light-activated chloride channel, is an attractive tool for neural inhibition as it can shunt membrane depolarizations. In this study, we assessed the effect of activating GtACR2 on in vivo hippocampal CA1 activity evoked by Schaffer collateral (SC) stimulation. Methods Adult male Wistar rats were unilaterally injected with 0.5 μL of adeno associated viral vector for induction of GtACR2-mCherry (n = 10, GtACR2 group) or mCherry (n = 4, Sham group) expression in CA1 pyramidal neurons of the hippocampus. Three weeks later, evoked potentials (EPs) were recorded from the CA1 subfield placing an optrode (bipolar recording electrode attached to an optic fiber) at the injection site and a stimulation electrode targeting SCs. Effects of illumination parameters required to activate GtACR2 such as light power densities (LPDs), illumination delays, and light-pulse durations were tested on CA1 EP parameters [population spike (PS) amplitude and field excitatory postsynaptic potential (fEPSP) slope]. Results In the GtACR2 group, delivery of a 10 ms light-pulse induced a negative deflection in the local field potential which increased with increasing LPD. When combined with electrical stimulation of the SCs, light-induced activation of GtACR2 had potent inhibitory effects on CA1 EPs. An LPD of 160 mW/mm2 was sufficient to obtain maximal inhibition CA1 EPs. To quantify the duration of the inhibitory effect, a 10 ms light-pulse of 160 mW/mm2 was delivered at increasing delays before the CA1 EPs. Inhibition of EPs was found to last up to 9 ms after the cessation of the light-pulse. Increasing light-pulse durations beyond 10 ms did not result in larger inhibitory effects. Conclusion Precisely timed activation of GtACR2 potently blocks evoked activity of CA1 neurons. The strength of inhibition depends on LPD, lasts up to 9 ms after a light-pulse of 10 ms, and is independent of the duration of the light-pulse given.